Job Satisfaction as a Mediator of Spiritual Leadership and Intention to Stay of Teaching Personnel - Muhammad Fajrul Islam Fasieh; Armanu Thoyib; Nanang Suryadi (Journal of Business and Management Review, 2023)
This study aimed to determine the role of spiritual leadership and job satisfaction in increasing the intention to stay employed among teaching personnel. This study was conducted at Darud Da'wah Wal Irsyad educational institution in Parepare City, South Sulawesi, Indonesia. Data collection used a non-probability sampling approach. Respondents collected in this study was 144. The data analysis method used partial least squares (PLS)-based structural equation modeling (SEM) using the SmartPLS 3.3 software application. The research findings noted that spiritual leadership and job satisfaction proved to have an effect on increasing the intention to stay of teaching personnel. Spiritual leadership has a direct impact on teaching personnel's intention to stay. Spiritual leadership has a direct effect on job satisfaction. Job satisfaction has a direct effect on intention to stay. In addition, the effect of spiritual leadership will be better if supported by job satisfaction in increasing the intention to stay of teaching personnel; in other words, job satisfaction partially mediates the relationship between spiritual leadership and intention to stay.